Relationships Between Mental Health, Emotion Regulation, and Meaning in Life of Frontline Nurses During the COVID-19 Outbreak - Chen, Sisi; Zhou, Wen; Luo, Ting; Huang, Lingzhi (Frontiers in Psychiatry, 2022)
Objective: To investigate the relationship between meaning in life, emotional regulation and mental health of frontline nurses during the delta virus epidemic. Methods: A cross-sectional survey was conducted in August 2021 among 105 nurses from the Second Xiangya Hospital, Central South University, Changsha China, who were deployed at the COVID-19 units in Zhangjiajie People's Hospital.The Chinese Meaning in Life Questionnaire,Emotion Regulation and Psychological Questionnaire for Emergent Events of Public Health were used to evaluate their meaning in life,emotion regulation and mental health .Their correlation and the moderating effect of emotion regulation were conducted. Results:Totally, 105 (100%) nurses responded.There were 14 males and 91 females and the mean age was (30.295±4.653) years.The average score of meaning in life and mental health of frontline nurses was 49.971±6.386 and 2.755±2.580,respectively.The meaning in life of frontline nurses was positively correlated with cognitive reappraisal,and negatively correlated with expressive suppression and mental health.Mental health was negatively correlated with cognitive reappraisal and positively correlated with expressive suppression.The emotional regulation of frontline nurses has a moderating effect between meaning in life and mental health. Conclusion: Meaning in life and emotion regulation of frontline nurses were significantly correlated with mental health under the effects of the COVID-19 pandemic. Changing the emotion regulation of frontline nurses,strengthening cognitive reappraisal,and weakening expressive suppression could reduce the predictive effect of meaning in life on mental health.